2014
DOI: 10.1016/j.aquaculture.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolism of unsaturated fatty acids in Octopus vulgaris hatchlings determined by incubation with 14C-labelled fatty acids added directly to seawater as protein complexes

Abstract: 25The high mortalities observed during Octopus vulgaris paralarvae culture have been 18:2n-6, 18:3n-3, 20:4n-6 (ARA), 20:5n-3 (EPA) or 22:6n-3 (DHA), which were added 33 directly to the seawater as their potassium salts bound to bovine serum albumin (BSA). 34A control treatment without [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 40 publications
10
58
0
Order By: Relevance
“…Molluscs have been regarded as having active FA elongation pathways and studies in O. vulgaris have shown that this is also the case in cephalopods (Monroig et al, 2012b;Reis et al, 2014). Indeed, the present data clearly showed that the cuttlefish Elovl had the ability to elongate C18 and C20 PUFA substrates, but showed no activity towards…”
Section: Accepted M Manuscriptmentioning
confidence: 49%
See 1 more Smart Citation
“…Molluscs have been regarded as having active FA elongation pathways and studies in O. vulgaris have shown that this is also the case in cephalopods (Monroig et al, 2012b;Reis et al, 2014). Indeed, the present data clearly showed that the cuttlefish Elovl had the ability to elongate C18 and C20 PUFA substrates, but showed no activity towards…”
Section: Accepted M Manuscriptmentioning
confidence: 49%
“…The phylogenetic and sequence analyses, as well as the functional characterisation hatchlings (Reis et al, 2014). While current data suggest that ∆6 desaturase appear not to exist in cephalopods and putative ∆8 desaturase have not been yet confirmed, we postulate that EPA and ARA are indeed EFA for cephalopods including S. officinalis.…”
Section: Accepted M Manuscriptmentioning
confidence: 51%
“…High levels of this FA has been also found in previous studies in O. vulgaris (Navarro and Villanueva, 2003;Reis et al, 2014), so that further studies are necessary to figure out the reason for its conservation.…”
Section: Biochemical Composition Variation Throughout the Embryonic Dmentioning
confidence: 58%
“…Since protein is the main corporal component of the cephalopods and it has a vigorous amino acid metabolism (Lee, 1994;Villanueva and Norman, 2008) there is a large amino acid requirement for maintaining optimal growth and supplying energy. In addition, from their lipid composition and that of their natural prey, it can be deduced that early stages of cephalopod must require a food rich in polyunsaturated fatty acids (PUFA) (Monroig et al, 2012a,b;Navarro and Villanueva, 2000;Reis et al, 2014).…”
mentioning
confidence: 99%
“…Previous investigations on O. vulgaris [6,10,33] and S. officinalis [20] revealed that cephalopods possess active desaturase and elongase enzymes involved in the biosynthesis of PUFAs including NMI FAs. Using the common octopus O. vulgaris as model species, the present study aimed to expand our knowledge of roles that further desaturases and elongases could have on PUFA biosynthesis in cephalopods.…”
Section: Discussionmentioning
confidence: 99%